2009
DOI: 10.1007/s00232-009-9187-z
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Two Different Types of Ion Channels by Amphotericin B in Human Erythrocyte Membranes

Abstract: The polyene antibiotic amphotericin B (AmB) is known to form aqueous pores in lipid membranes and biological membranes. Here, membrane potential and ion permeability measurements were used to demonstrate that AmB can form two types of selective ion channels in human erythrocytes, differing in their interaction with cholesterol. We show that AmB induced a cation efflux (negative membrane polarization) across cholesterol-containing liposomes and erythrocytes at low concentrations (< or =1.0 x 10(-6) M), but a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…First, in cones, this phenomenon is not dependent on diffusion of Ca 2+ between the cell and the pipette, as the spontaneous increase in coupling was expressed in perforated patch recordings, even in combination with EGTA in the pipette solution. This, therefore, excludes the possibility of a Ca 2+ entry through hypothetical Ca 2+ -permeable pores formed by amphotericin-B in the patch membrane (Romero et al, 2009; see also ‘Results’). Second, our recordings in whole cell patch clamp with buffered pipette Ca 2+ levels, made in close proximity to the GJs, strongly suggest that changes in free [Ca 2+ ] i in cones are not responsible for the expression of this phenomenon.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…First, in cones, this phenomenon is not dependent on diffusion of Ca 2+ between the cell and the pipette, as the spontaneous increase in coupling was expressed in perforated patch recordings, even in combination with EGTA in the pipette solution. This, therefore, excludes the possibility of a Ca 2+ entry through hypothetical Ca 2+ -permeable pores formed by amphotericin-B in the patch membrane (Romero et al, 2009; see also ‘Results’). Second, our recordings in whole cell patch clamp with buffered pipette Ca 2+ levels, made in close proximity to the GJs, strongly suggest that changes in free [Ca 2+ ] i in cones are not responsible for the expression of this phenomenon.…”
Section: Discussionmentioning
confidence: 92%
“…However, the fact that we observed this phenomenon in perforated patch clamp recordings, a technique known to cause minimal disturbance to the intracellular environment, makes it unlikely that in mouse cones, it is caused by pipette-cell dialysis (we could exclude an unintended rupture of the patch membrane, since the amphotericin-B present in our pipette solution would have perforated the cell membrane, depolarizing it close to 0 mV and shunting the photovoltages—effects that we indeed observed when going whole cell at the end of recordings to stain the neurons with Lucifer Yellow, LY). Nonetheless, we examined the remote possibility that amphotericin-B (nominally 400 µM) formed Ca 2+ -permeable pores (Romero et al, 2009) and that the diffusion of calcium ions from the pipette into the cone led to an opening of GJs (Ca 2+ traces are normally present in the high purity water used for intracellular solutions). In four of five cones recorded with 1 mM EGTA in the pipette ( EGTA zero Ca 2+ perforated patch solution), we observed the same progressive increase in coupling (Figure 4, blue lines).…”
Section: Resultsmentioning
confidence: 99%
“…The nonaqueous AmB channels can also be inserted at the lipid rafts as suggested by the shift from negative to positive activation energies of the K ϩ permeability that was measured in human erythrocyte membranes treated with AmB concentrations higher than the threshold value at which aqueous pores are formed (22). In this regard, it is important that AmB also forms ion channels in sterol-free small liposomes (23), which have curvatures in the range predicted for locally curved nanoscale raft domains (24).…”
Section: The Formation Of Amb Ion Channels In the Nonraft And Raft Mementioning
confidence: 96%
“…1B). Thus, AmB exerts a maximal effect on the secretion of TNF-␣ in immune cells at 4 M (43) and 6.4 M (44), which are concentrations above the threshold value for the formation of aqueous pores by AmB (10,22). In fact, the differential role of K ϩ efflux in the secretion of IL-1ß compared to TNF-␣ is shown clearly in the data obtained in THP-1 cells that indicated that when the AmB concentration was raised from 0.625 M to 5 M, the secretion of TNF-␣ increased by about 30-fold whereas the secretion of IL-1ß increased by only 4-fold (94).…”
Section: The Development Of Amb Toxicity and Resistance In Cholesteromentioning
confidence: 99%
“…These studies were devoted primarily to the pore-formation process, i.e., their membrane binding, partitioning and self-aggregation [11,12], and secondly to the physiologic implications in the case of different cell types. The studies of the nystatin and amphotericin B activity have demonstrated the suppression of growth and the death of fungal and leishmanial cells [1315], while in various mammalian cells morphological responses and cellular ion concentration changes were found [1619]. Nystatin has been used in experiments investigating the electrical properties of different tight epithelia, such as mammalian urinary bladder and colon epithelia, which characterized the conductances of the nystatin transmembrane pores for Na + , K + and Cl - [20,21].…”
Section: Introductionmentioning
confidence: 99%